The Determinants of Purchase Intention through Social Media Platform: A Quantitative Research in Malaysia - Jayanty KUPPUSAMY; Haritha MURUGAN; Ajitha ANGUSAMY (Communications of International Proceedings, 2025)
Social media has become an important marketing tool for businesses. With the increase in social media users, this further accelerated the power of social media. Businesses used social media platforms to market their products or services. Studies in this area, however, is limited specifically from a Malaysian context, indicating a research gap. The objective of the study is to investigate the factors that influence purchase intention through social media platforms. The chosen factors are content quality, social proof and influencer marketing. A quantitative research design is used. The respondents are social media users. The sampling method used is convenience sampling. A total of 200 respondents participated in this online survey. The analysis was done using multiple regression methods and the result revealed that all three factors influence purchase intention. The findings underline the importance of content quality, social proof and influencer marketing influencing purchase intention. The strongest predictor is social proof. This indicates to ensure there is an effective intention to purchase, there must be social proof in addition to other factors. This study provides significant information for firms wanting to optimize their digital marketing strategy, ensuring increased consumer interaction and conversion rates.
Keywords: content quality; social proof; influencer marketing; social media platforms; purchase intention